1984
DOI: 10.1084/jem.160.6.1901
|View full text |Cite
|
Sign up to set email alerts
|

Inherited deficiency of the Mac-1, LFA-1, p150,95 glycoprotein family and its molecular basis.

Abstract: The lymphocyte function-associated 1 (LFA-1), ~ Mac-l, and p150,95 molecules constitute a family of structurally and functionally related, high molecular weight, human leukocyte surface glycoproteins (1). Each molecule contains an a and a 3 subunit noncovalently associated in an al31 structure. The 3 subunits of Mr 95,000 in each of these three molecules are identical. The molecules are distinguished by their a subunits, which have different isoelectric points, molecular weights, and cell distributions, and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
190
3
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(206 citation statements)
references
References 37 publications
(25 reference statements)
11
190
3
2
Order By: Relevance
“…The leukocyte adhesion deficiency-I phenotype in humans and cattle (8,9,(42)(43)(44), as well as the defective T cell function and spontaneous skin ulceration seen in CD18 null mice emphasize that ␤ 2 integrins are critically important for host defense. Although LFA-1-deficient mice have deficits in experimental tumor models and increased mortality to gram (ϩ) sepsis with Streptococcus pneumoniae, they exist without apparent spontaneous illness in conventional mouse housing facilities (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leukocyte adhesion deficiency-I phenotype in humans and cattle (8,9,(42)(43)(44), as well as the defective T cell function and spontaneous skin ulceration seen in CD18 null mice emphasize that ␤ 2 integrins are critically important for host defense. Although LFA-1-deficient mice have deficits in experimental tumor models and increased mortality to gram (ϩ) sepsis with Streptococcus pneumoniae, they exist without apparent spontaneous illness in conventional mouse housing facilities (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Patients deficient in ␤ 2 integrin expression (the leukocyte adhesion deficiency-I phenotype) display leukocytosis, impaired wound healing, and particular susceptibility to recurrent microbial infection due in part to an inability to recruit leukocytes from the circulation and form pus (8,9). Mice deficient in CD18 (10) display a similar phenotype, with leukocytosis and susceptibility to bacterial infection (reviewed in Ref.…”
mentioning
confidence: 99%
“…C1-INH deficiency has been suggested to be associated with increased vascular permeability, thus oedema (Bracho, 2005). Current knowledge state that CR3 and CR4 deficiencies occur simultaneously in patients with leukocyte adhesion deficiency (LAD) type 1 due to genetic defects in the CD18 (β-subunit of both complement receptors) gene, ITGB2 (Springer et al, 1984(Springer et al, , 1986Roos et al, 2002;Bernard Cher et al, 2012). The lack of memory/effector CD8+ T cells and neutrophils in these patients result in reduced phagocytic response to bacteria and yeast.…”
Section: Complement Regulators and Receptorsmentioning
confidence: 99%
“…The lack of memory/effector CD8+ T cells and neutrophils in these patients result in reduced phagocytic response to bacteria and yeast. Most clinical features are probably the result of CR3 deficiency of neutrophils and monocytes (Springer et al, 1984(Springer et al, , 1986. The reduced ability of such neutrophils to adhere to various substances, including complement-derived chemo-attractants (e.g.…”
Section: Complement Regulators and Receptorsmentioning
confidence: 99%
“…Although these patients had a persistent leukocytosis, very few leukocytes accumulated at infected, necrotic lesions. In 1984 several groups demonstrated that these patients' leukocytes were missing CDt la,b,c/CD18 and subsequent work has demonstrated that the primary genetic defects are in CD18, the shared subunit (2)(3)(4)(5)23,24). Thus, the inability of leukocytes to adhere to endothelium or other particles because of an inherited defect in adhesive molecules prevents accumulation of leukocytes at sites of microbial invasion and results in severe, recurrent infections.…”
Section: Integrinsmentioning
confidence: 99%